2011
DOI: 10.1007/s00259-011-1956-0
|View full text |Cite
|
Sign up to set email alerts
|

Coronary risk factors and myocardial blood flow in patients evaluated for coronary artery disease: a quantitative [15O]H2O PET/CT study

Abstract: BackgroundThere has been increasing interest in quantitative myocardial blood flow (MBF) imaging over the last years and it is expected to become a routinely used technique in clinical practice. Positron emission tomography (PET) using [15O]H2O is the established gold standard for quantification of MBF in vivo. A fundamental issue when performing quantitative MBF imaging is to define the limits of MBF in a clinically suitable population. The aims of the present study were to determine the limits of MBF and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 37 publications
(50 reference statements)
4
41
2
Order By: Relevance
“…Although methodologic considerations between imaging protocols and patient selection may account for some of these discrepancies, the selection of an optimal threshold to reproduce such a high diagnostic yield may prove difficult in clinical practice. Studies in patients without CAD have clearly demonstrated that the reference range of hyperemic MBF is relatively broad because of physiologic variation in minimal coronary microvascular resistance, which is related to patient characteristics such as age, sex, and CAD risk factors (11,(18)(19)(20). Because hyperemic MBF is governed by the (potential) presence of an epicardial coronary lesion and microvascular resistance, a cutoff value to identify an obstructive coronary lesion will vary according to the conductance capacity of the microvascular bed in each individual patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although methodologic considerations between imaging protocols and patient selection may account for some of these discrepancies, the selection of an optimal threshold to reproduce such a high diagnostic yield may prove difficult in clinical practice. Studies in patients without CAD have clearly demonstrated that the reference range of hyperemic MBF is relatively broad because of physiologic variation in minimal coronary microvascular resistance, which is related to patient characteristics such as age, sex, and CAD risk factors (11,(18)(19)(20). Because hyperemic MBF is governed by the (potential) presence of an epicardial coronary lesion and microvascular resistance, a cutoff value to identify an obstructive coronary lesion will vary according to the conductance capacity of the microvascular bed in each individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a stable heart rate below 65 bpm (either spontaneous or after the administration of oral or intravenous metoprolol) underwent a CT scan for calcium scoring and CTCA as previously described (11). All CT scans were analyzed with a 3-dimensional workstation (Brilliance, Philips) by an experienced radiologist and cardiologist who were masked to the ICA results.…”
Section: Ctcamentioning
confidence: 99%
See 1 more Smart Citation
“…Upon exclusion of patients with atherosclerosis, gender-related differences in coronary microvascular function remained substantial. Last year, a comparable study by Danad et al was published in this journal [6]. Although both studies linked a number of traditional cardiovascular risk factors to coronary microvascular dysfunction, the most prominent similarity between them is the impact of gender.…”
mentioning
confidence: 82%
“…4, 5 Previous CTP studies used absolute MBF thresholds in mL/100 g/min to discriminate flow-limiting CAD, 6-10 but the absolute MBF can vary because of factors other than the degree of coronary artery stenosis. 11- 14 Patients with extensive non-obstructive CAD may show GOTO Y et al…”
Section: Study Populationmentioning
confidence: 99%